2015
DOI: 10.1016/j.ebiom.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Primary Cytomegalovirus Infection in Pregnancy

Abstract: BackgroundCytomegalovirus (CMV) is the leading infectious agent causing congenital sensorineural hearing loss and psychomotor retardation. CMV vaccine is currently unavailable and treatment options in pregnancy are limited. Susceptible pregnant women caring for children are at high risk for primary infection. CMV educational and hygienic measures have the potential to prevent primary maternal infection.MethodsA mixed interventional and observational controlled study was conducted to investigate the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
183
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(197 citation statements)
references
References 29 publications
4
183
0
10
Order By: Relevance
“…The value of HCMV screening as part of the prenatal program has become a subject of worldwide discussion (e20 Especially HCMV-IgG-negative pregnant women benefit from hygiene counseling on how to prevent HCMV-transmission (Box 2); a significant preventative effect of hygiene counseling aimed at HCMV exposure prophylaxis was demonstrated (21,22). In a French hospital, the rate of seroconversion during pregnancy was reduced by half from 0.4% to 0.2% (21).…”
Section: Protection Of Expectant Mothersmentioning
confidence: 99%
See 2 more Smart Citations
“…The value of HCMV screening as part of the prenatal program has become a subject of worldwide discussion (e20 Especially HCMV-IgG-negative pregnant women benefit from hygiene counseling on how to prevent HCMV-transmission (Box 2); a significant preventative effect of hygiene counseling aimed at HCMV exposure prophylaxis was demonstrated (21,22). In a French hospital, the rate of seroconversion during pregnancy was reduced by half from 0.4% to 0.2% (21).…”
Section: Protection Of Expectant Mothersmentioning
confidence: 99%
“…The risk of primary infection is particularly high in mothers with HCMV shedding asymptomatic children (seroconversion rate of up to 24% per year [23]). In a current controlled HCMV prevention study conducted in Italy, evaluating hygiene counseling in pregnant women caring for at least one infant/toddler, the French outcomes were exceeded with a seroconversion rate reduction from 7.6% to 1.2% (22). After the introduction of the rubella vaccine for active immunization against the disease, a tremendous reduction in the incidence of congenital rubella syndrome (CRS) was observed (e22).…”
Section: Protection Of Expectant Mothersmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a recent randomized study demonstrated that the aforementioned measures significantly prevented maternal infections and negative consequences for the newborns [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Susceptible pregnant women who have contact with young children are at risk of acquiring a primary CMV infection (8). Strategies that reduce child-to-child CMV transmission, including CMV vaccines, may reduce child-to-mother transmission and thus reduce the burden of congenital CMV infection (9,10).…”
mentioning
confidence: 99%